Comparative Study of Processing Student Learning Results Scores using Microsoft Excel with the RDM (Digital Madrasah Report Card) Website - Haury, Ahmad Musyadad; Widodo, Suprih; Hikmawan, Rizki (International Journal Software Engineering and Computer Science (IJSECS), 2024)
This research explores the comparison of Microsoft Excel and Madrasah Digital Report Cards (RDM) in processing student grades into report cards using qualitative methods. In evaluating the advantages and disadvantages of each platform, this research highlights practicality and affordability as important elements in selecting a value management tool. Microsoft Excel is known as a widely recognized tool, while RDM adds practicality through web-based accessibility. Data security is a key consideration, with RDM providing a higher level of protection compared to Excel's inherent security risks. Customization is a key factor, where Excel's high level of flexibility is balanced with a well-organized RDM template structure, which is in line with the needs of the madrasah curriculum. The integration factor is also a determining factor, as Excel requires greater technical effort while RDM is designed to facilitate integration within the madrasa education ecosystem. The choice between Excel and RDM is recommended depending on the specific priorities and needs of the madrasah. For those focused on flexibility and sustainability, Excel may be a more suitable choice. At the same time, RDM offers a more appropriate solution for those who prioritize accessibility, data security, and easy integration. Practical advice is given to madrasah educational institutions to consider the unique characteristics of their environment and the goals they wish to achieve. In-depth evaluation of security, affordability, customization, and integration guides platform selection to support the effectiveness and efficiency of processing student grades into report cards.